Sexual maturity as risk for development of deviant behaviours in pig production systems with entire males - 1. Nakov, D., Trajchev, M., Hristov, S., Stanković, B., Cincović, M., Zlatanović, Z., Bojkovski, J. (Veterinarski Glasnik, 2021)
Male piglets are castrated primarily to avoid the unpleasant boar taint in meat, and additionally for the predisposition of castrates to accumulate fat and for their lower risk of developing unwanted behaviours. There are two main strategies available for withdrawing from surgical castration: one is immunocastration and the other is to raise entire male pigs or boars. Additionally, raising intact boars is more profitable because of the production of carcasses with lean meat and better feed conversion. Boars (compared to castrates) exhibit more aggressive, sexual, damaging social behaviour and reduced feeding behaviour with a lower prevalence of sickness behaviour as a result of good health and low susceptibility to chronic inflammation. In this review, the behaviours specific for boars as a result of sexual maturity are reviewed, with an overview of differences in the behaviour of surgically castrated barrows, immunocastrates and boars reared in group-housed systems. The raising of boars allows for good welfare of these animals in early life, but later, on reaching sexual maturity, the welfare of boars can be diminished because of their propensity to aggression and more mounting behaviour than castrates. Innovations in the breeding and management of boars are needed to improve their performance and to reduce welfare implications of these animals raised in social groups, and in particular to minimize deviant behaviours towards pen mates.
Keywords: boar, castration, damaging behaviour, pubertal behaviour